Biomarkers in the serum, synovial fluid and articular cartilage show promising utility in patients with femoroacetabular impingement: a systematic review. Issue 3 (14th November 2017) - Kay, Jeffrey; Memon, Muzammil; Zou, Vito Z; Duong, Andrew; Simunovic, Nicole; Bonin, Nicolas; Safran, Marc R; Ayeni, Olufemi R
Abstract : Importance: Biomarkers have promising potential to provide a cost-effective tool to identify patients with femoroacetabular impingement (FAI) who are most at risk and who may benefit most from early joint preservation surgery. Objective: To assess the potential role of biomarkers in the diagnosis and prognosis of FAI. Evidence review: Three databases (PubMed, Ovid (MEDLINE) and Embase) were searched on 20 August 2017 from database inception, and two reviewers independently and in duplicate screened the resulting literature. Methodological quality of all included papers was assessed using the Methodological Index for Non-Randomized Studies criteria. The results are presented in a narrative summary fashion using descriptive statistics including means, proportions and ranges. Findings: Seven studies (one retrospective laboratory series and six controlled laboratory studies) were identified including a total of 227 patients. The mean age of the patients was 41.6 years (range: 13–80), with a mean follow-up period of 29.9 months (SD=3.2). Markers of articular cartilage breakdown, including cartilage oligomeric matrix protein (COMP) and fibronectin–aggrecan complex (FAC), were identified in high concentrations in the serum and synovial fluid of patients with FAI, respectively. Moreover, mRNA expression of catabolic cytokines in the articular cartilage of patients with FAI has been reported. Conclusions and relevance: Although not yet used in clinical settings, several biomarkers of articular cartilage damage have been identified in the serum, synovial fluid and articular cartilage of patients with FAI. These findings provide promising insight into the potential role of biomarkers in guiding clinical practice and assisting with patient selection and preoperative counselling in patients with FAI and should be evaluated further. Level of evidence: IV, systematic review of level III and IV studies.